Linguistic Complexity in Hadith: An Examination of the Role and Origins of 'Al-kalimat al-mubtakirah' in Hadith - Machsun, Mohamad Anang Firdaus (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This research investigates an intriguing phenomenon concerning the use of the Arabic language in the narrations of Hadith. Despite Prophet Muhammad's acknowledged fluency in the Arabic language, there are instances of foreign words, known as "gharabah," used in some hadith. One striking example is the term "al-kalimat al-mubtakirah," which constitutes a newly coined vocabulary by Prophet Muhammad and was not fully comprehended by his companions. This study aims to examine three crucial aspects related to this phenomenon. Firstly, it identifies patterns within the al-kalimat al-mubtakirah that have never been heard before in the Arabic language, whether in the form of words, phrases, or sentences. Secondly, it delves deeper into the eloquence of prophethood and the role of foreign words (gharabah) in Prophet Muhammad's hadith. Thirdly, it attempts to elucidate the reasons behind the emergence of foreign words in Prophet Muhammad's hadith. The methodology employed in this research is literature review, with a focus on the examination of al-kalimat al-mubtakirah related to the Prophet's eloquence in hadith and the concept of gharabah in the science of rhetoric (balaghah). The research findings reveal the following: Firstly, the innovative words coined by Prophet Muhammad demonstrate a high level of linguistic proficiency. Al-kalimat al-mubtakirah encompasses three distinct patterns, namely words, phrases, and sentences. Secondly, the foreign words in Prophet Muhammad's hadith are regarded as good foreign words (al-gharib al-hasan). Their usage is uncommon in everyday Arabic language due to their higher level of linguistic complexity compared to the common understanding. Thirdly, this research identifies six reasons why foreign words appear in Prophet Muhammad's Hadith.